THE IMPORTANCE OF DIGITAL MARKETING STRATEGIES IN THE SOCIETY 5.0 ERA FOR MSMES IN JAMBI CITY - Trilakshmi, Nasta (Management Studies and Business Journal (PRODUCTIVITY), 2025)
This study examines the importance of digital marketing strategies for MSMEs in Jambi City in facing the challenges of the Society 5.0 era through a literature review approach with a focus on market expansion, promotion cost efficiency, and increased profitability. With a significant MSME population in Jambi City as part of more than 99% of the total national business units, digital transformation has become a strategic imperative for MSMEs to increase competitiveness and achieve sustainable growth. The analysis shows that the adoption of digital marketing has a positive correlation with the performance of MSMEs, where behavioral control factors and subjective norms have a significant effect on the intention of using digital platforms. The structured digital transformation program in Jambi City showed high effectiveness with 80% of participants successfully registering for independent NIB, 88% routinely recording digital finances, and 75% actively creating promotional content. The use of social media and digital platforms allows MSMEs to reach a wider market by reducing promotional costs by up to 70% compared to conventional methods, while increasing profit potential through the expansion of consumer segmentation. However, limited capital, human resources, and technological infrastructure are still major obstacles. A sustainable innovation strategy that integrates local wisdom with digital technology has been proven to increase the competitive advantage of MSMEs and provide a significant return on investment. Recommendations include the development of holistic capacity building, access to technology financing, and the creation of a supportive digital ecosystem for the transformation of MSMEs towards Society 5.0 that prioritizes sustainable profitability.